The Distribution of Buceros rhinoceros and Awareness of Its Conservation Status - Mohd Azlan, Jayasilan; Abas, Said; Sim, Lee Kheng; Tisen, Oswald Braken (Springer International Publishing, 2016)
A rapid survey on the distribution of hornbills in Santubong National Park, Sarawak, East Malaysia, was carried out in April 2013 using point sampling technique at various locations around the park. Only the Rhinoceros hornbill, Buceros rhinoceros , was recorded, with a total of 45 independent calls and 15 observations at 10 locations around the protected area, mostly during early mornings and late evenings from 162 h of survey. Most of Rhinoceros hornbills were observed in pairs (73 %), while a single observation recorded at least ten individuals at a location. Additionally, local communities were interviewed to collect information on the occurrence, status, ecology and perception on Hornbill conservation in Santubong National Park. A standard questionnaire was designed to meet the purpose of this study. This survey was conducted on local communities from fi ve local villages around Santubong National Park, local and international tourist visiting touristic areas in Santubong peninsula. In general the awareness on the conservation needs and status of the hornbill is high suggesting that the communities are interested and supportive of conservation related activities. Based on the socio-economic and ecological survey, the surrounding habitat of this protected area need to be protected through park extension that will increase connectivity between nearby forest patches which in turn may ensure the long term viability of the Rhinoceros hornbill in Santubong National Park.